Designing with video Focusing the user-centred design process - Ylirisku, Salu.; Buur, Jacob; SpringerLink (Online service) (London : Springer London, 2007)
Digital video for user-centred co-design is an emerging field of design, gaining increasing interest in both industry and academia. It merges the traditions of design ethnography, participatory design, interaction analysis, scenario-based design, and usability studies into an integrated approach, which values the designer$1 (Bs capacity to study and change the world creatively. Designing with Video: Focusing the User-centred Design Process covers the whole user-centred design project. The book illustrates in detail how digital video can be utilised throughout a design process, from the early user studies, through making sense of the video content and envisioning the future with video scenarios, to provoking change with video artefacts. A must-read for those wishing to create more value through insightful design, the text builds upon a wealth of real, first-hand case studies both in academic and industrial contexts, and is complemented by video excerpts. Teachers, students and professionals in design will all benefit from this approach for developing new ways of enhancing their design processes.s
Video in design -- Studying what people do -- Making sense and editing videos -- Envisioning the future -- Provoking change.
Keywords: Engineering; User interfaces (Computer systems).; Computer-aided engineering; Computational intelligence; Engineering design; Engineering; Engineering Design; Computational Intelligence; Computer-Aided Engineering (CAD, CAE) and Design; User Interfaces and Human Computer Interaction; Electronic books